Fine-tuning the diradical character of molecular systems via the heteroatom effect. Issue 9 (8th January 2020) - Wang, Wenxiang; Ge, Lingbing; Xue, Guodong; Miao, Fang; Chen, Pingan; Chen, Hanjiao; Lin, Yiwei; Ni, Yong; Xiong, Jingyuan; Hu, Yuanyuan; Wu, Jishan; Zheng, Yonghao
Abstract : Heteroatoms were introduced as a novel modification strategy for fine-tuning the diradical character of molecular systems. Abstract : Heteroatoms were introduced as a novel modification strategy for fine-tuning the diradical character of molecular systems. Both the diradical character and the singlet–triplet energy gaps of diketopyrrolopyrrole based phenoxyl diradicaloids decreased as the size of the substituted heteroatoms (from O, S to Se atom) increased.